The Adversarial Approach in the Pre-trial Phase of Prosecution - Pushkarev, Viktor Victorovich; Trishkina, Ekaterina Alekseevna; Tokareva, Ekaterina Viktorovna; Cuong, Bui Tran; Shepeleva, Olga Rinatovna (Cuestiones Políticas, 2020)
The confrontational or adversarial approach is one of the main factors that forms the basis of the criminal justice system. However, its application in the pre-trial phase is limited. Therefore, this document aims to demonstrate the importance of analyzing theoretical and practical problems. The choice of documentary and casuistic methodology allowed the following conclusions to be reached: Currently, the Russian police are undergoing changes that aim to humanize the criminal process, to solve fundamental challenges in the protection of the rights, liberty and interests of a person in the pre-trial investigation that will guarantee the confrontation system in criminal proceedings. We conducted a comparative legal investigation and analyzed criminal case files, as well as the results of questionnaire surveys conducted among investigators and attorneys. Overall, the results represent the actual state of cases in the pre-trial phase and help determine areas of development. We propose feasible changes to the criminal procedure legislation of the Russian Federation that will eliminate the disparity between some of its regulations and the requirements of the confrontation system in general.